2020
DOI: 10.1200/jco.2020.38.15_suppl.9008
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of pembrolizumab (pembro) plus platinum doublet chemotherapy and radiotherapy as first-line therapy for unresectable, locally advanced stage III NSCLC: KEYNOTE-799.

Abstract: 9008 Background: KEYNOTE-799 (NCT03631784) evaluates pembro plus concurrent chemoradiation therapy (CCRT) in pts with unresectable, locally advanced stage III NSCLC. Methods: In this phase 2, nonrandomized, open-label trial, pts with previously untreated, unresectable, pathologically confirmed stage IIIA–C NSCLC with measurable disease (RECIST 1.1) received up to 17 cycles of pembro 200 mg Q3W starting with cycle 1 plus standard thoracic radiotherapy (60 Gy in 30 daily 2-Gy fractions) in cycles 2–3 and invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Of those, 56 duplicate studies were excluded. After careful screening and assessment, 11 clinical trials involving 1,113 patients with NSCLC were finally included in the analysis (6,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Figure 1 illustrates the flow diagram of study selection.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Of those, 56 duplicate studies were excluded. After careful screening and assessment, 11 clinical trials involving 1,113 patients with NSCLC were finally included in the analysis (6,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Figure 1 illustrates the flow diagram of study selection.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…The sequence of radiotherapy combined with ICI is still controversial and the use of ICI after radiotherapy may reduce severe pneumonia just as PACIFIC and PEMBRO-RT study did. But KEYNOTE-799 indicated that chemoradiotherapy and simultaneous ICI were well tolerated, and the incidence of pneumonia above grade 3 was 3.4% (41).…”
Section: Discussionmentioning
confidence: 99%
“…Presented at the ASCO meeting 2020, the preliminary results, with recruitment yet to be completed, of the phase II, non-randomised trial KEYNOTE-799, with pembrolizumab concomitant to CRT, show that the overall response rate (ORR) was 67% in patients with carboplatin and paclitaxel-based ChT, and 56.6% with platinum and pemetrexed. The percentage of grade 5 pneumonitis was 3.5% with carboplatin + paclitaxel [ 78 ]. Likewise, results have been presented for atezolizumab prior and subsequent to CRT treatment, with an ORR of 82.4% for PD-L1 negative patients and 90.9% for PD-L1 positive.…”
Section: Combination Of Immunotherapy and Definitive Radiotherapy +/− Chemotherapy Strategymentioning
confidence: 99%